2008
DOI: 10.1007/s11655-008-0251-9
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study on the effect of a combined treatment of traditional Chinese medicine and Western medicine on the relapse and metastasis of 222 patients with stage II and III colorectal cancer after radical operation

Abstract: The combined therapy of TCM and WM may have great clinical value and a potential for decreasing the relapse or metastasis rate in stage II and III colorectal cancer after conventional WM therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The relapse/metastasis rate in the combined group at 1-, 2-, 3-, 4-, and 5-years was 0 (0/98), 2.04% (2/98), 11.69% (9/77), 14.06% (9/64), and 21.28% (10/47), respectively (18). In the group given WM, the relapse/metastasis rates were 4.80% (5/104), 16.35% (17/104), 21.65% (21/97), 25.93% (21/81), and 38.18% (21/55), respectively, for 1-, 2-, 3-, 4-and 5-years (19). The median relapse/metastasis time was 26.5 months in the combined group and 16.0 months in the WM group.…”
Section: Cryptotanshinone Targets Tumor-initiating Cells Through Downmentioning
confidence: 96%
See 1 more Smart Citation
“…The relapse/metastasis rate in the combined group at 1-, 2-, 3-, 4-, and 5-years was 0 (0/98), 2.04% (2/98), 11.69% (9/77), 14.06% (9/64), and 21.28% (10/47), respectively (18). In the group given WM, the relapse/metastasis rates were 4.80% (5/104), 16.35% (17/104), 21.65% (21/97), 25.93% (21/81), and 38.18% (21/55), respectively, for 1-, 2-, 3-, 4-and 5-years (19). The median relapse/metastasis time was 26.5 months in the combined group and 16.0 months in the WM group.…”
Section: Cryptotanshinone Targets Tumor-initiating Cells Through Downmentioning
confidence: 96%
“…There are numerous clinical reports indicating that patients benefit from TCM treatment including Lin et al (18), which observed 173 cases of non-small cell lung cancer (NSCLC) patients, post-surgery, with two years of treatment with standard chemoprevention alone or combined with TCM herbs: The result of this study indicated that the relapse and distant metastasis rate of patients in the TCM group was 45.09% and the control group was 50.6%. Yang et al (19) evaluated the effectiveness of comprehensive TCM treatment in reducing the relapse and metastasis of stage II and III colorectal cancer based on conventional Western medicine (WM) therapy: In this study, 222 patients were recruited and assigned to two groups based on whether or not they were additionally treated with TCM comprehensive therapy. The relapse/metastasis rate in the combined group at 1-, 2-, 3-, 4-, and 5-years was 0 (0/98), 2.04% (2/98), 11.69% (9/77), 14.06% (9/64), and 21.28% (10/47), respectively (18).…”
Section: Cryptotanshinone Targets Tumor-initiating Cells Through Downmentioning
confidence: 99%
“…There were 222 patients included into the trial with CRC on stage II or II diagnose; staging standard was referred to the guidelines of the International Union Against Cancer (IUAC). Patients were combined into 2 groups: treated with conventional WM (meant as R0 radical operation or chemotherapy or/and radiotherapy according to National comprehensive cancer network (NCCN) clinical guidelines) and treated with WM combined with TCM, such as: Sijunzi Decoction, Chaihu Shugan Powder, Bazhen Decoction, Huachansu Tablet, Quxie capsule, Pingxiao capsule [48]. The results showed that the relapse/metastasis rates in 1-, 2-, 3-, 4-, 5-year were lower in a group with TCM as adjunct therapy than in the group with chemotherapy alone.…”
Section: Treatmentmentioning
confidence: 99%
“…Although surgery, chemotherapy and radiotherapy [2][3][4] have been the mainstay of colorectal cancer treatment, traditional Chinese medicine (TCM) has the advantage of reducing cancer therapy-induced toxicity and is a popular form of complementary and alternative medicine (CAM) in China [5]. In recent years, with increased popularity with patients in China, the traditional Chinese medicine has been shown to further minimize the side effects of surgery, radiation and chemotherapy [6], increase immune function [7] and improve survival [8]. Gamellia sinensis O.Ktze has been a widely used and well-documented medicinal plant for centuries [9,10].…”
Section: Introductionmentioning
confidence: 99%